2013
DOI: 10.1021/nl4036687
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Chirality in Superficially Racemic Patchy Silver Films

Abstract: Chiral patchy particle films where morphological enantiomers exist in equal proportion are found to have significant circular dichroism. It is determined that the rotation direction during glancing angle deposition breaks the racemic symmetry, resulting in a distribution of material which enhances the chirality of one set of enantiomers relative to the other. Microscopic analysis and geometric chirality calculations reveal that the chirality of the bulk film results from incomplete cancellations of even strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 32 publications
(41 reference statements)
2
87
0
Order By: Relevance
“…Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref. Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref.…”
Section: Superposition Of Local Chiralitiesmentioning
confidence: 46%
See 3 more Smart Citations
“…Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref. Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref.…”
Section: Superposition Of Local Chiralitiesmentioning
confidence: 46%
“…[40] and ≈0.04° at normal incidence in ref. [36,37]. More importantly, we would like to point out that such an ultrabroadband superchiral response observed in our SPPCMs is originated from the formation of definite handedness in all microscale domains in the same sample and therefore it eliminates the problem of random local chiralities reported in refs.…”
Section: Superposition Of Local Chiralitiesmentioning
confidence: 54%
See 2 more Smart Citations
“…Particularly, our previous work also demonstrates that with the help of assembled polystyrene (PS) sphere array, a kind of shell-like chiral nanostructures can be achieved [29]. This kind of CPS can combine the magnetic or dielectric spheres to form chiral “Janus particles” [30] or “patchy particles” [31, 32] and will find potential applications in the colloid field. However, the cancellation effect originated from the PS array limited the related applications.…”
Section: Introductionmentioning
confidence: 99%